Benefits of adversity?! How life history affects the behavioral profile of mice varying in serotonin transporter genotype - Bodden, Carina; Richter, S. Helene; Schreiber, Rebecca S.; Kloke, Vanessa; Gerß, Joachim; Palme, Rupert; Lesch, Klaus-Peter; Lewejohann, Lars; Kaiser, Sylvia; Sachser, Norbert (Frontiers in Behavioral Neuroscience, 2015)
Behavioral profiles are influenced by both positive and negative experiences as well as the genetic disposition. Traditionally, accumulating adversity over lifetime is considered to predict increased anxiety-like behavior (“allostatic load”). The alternative “mismatch hypothesis” suggests increased levels of anxiety if the early environment differs from the later-life environment. Thus, there is a need for a whole-life history approach to gain a deeper understanding of how behavioral profiles are shaped. The aim of this study was to elucidate the effects of life history on the behavioral profile of mice varying in serotonin transporter (5-HTT) genotype, an established mouse model of increased anxiety-like behavior. For this purpose, mice grew up under either adverse or beneficial conditions during early phases of life. In adulthood, they were further subdivided so as to face a situation that either matched or mismatched the condition experienced so far, resulting in four different life histories. Subsequently, mice were tested for their anxiety-like and exploratory behavior. The main results were: (1) Life history profoundly modulated the behavioral profile. Surprisingly, mice that experienced early beneficial and later escapable adverse conditions showed less anxiety-like and more exploratory behavior compared to other life histories. (2) Genotype significantly influenced the behavioral profile, with homozygous 5-HTT knockout mice displaying highest levels of anxiety-like and lowest levels of exploratory behavior. Our findings concerning life history indicate that the absence of adversity does not necessarily cause lower levels of anxiety than accumulating adversity. Rather, some adversity may be beneficial, particularly when following positive events. Altogether, we conclude that for an understanding of behavioral profiles, it is not sufficient to look at experiences during single phases of life, but the whole life history has to be considered.